A new genus of the tribe Caliscelini (Hemiptera, Fulgoroidea, Caliscelidae) from Vietnam - Gnezdilov, Vladimir M.; Bourgoin, Thierry; Soulier-Perkins, Adeline (Zootaxa, 2014)
A new genus Annamatissus Gnezdilov et Bourgoin gen. nov., including the new species, Annamatissus tami Gnezdilov et Soulier-Perkins sp. nov. is described in the family Caliscelidae from the Bi-Doup massif in Lam Dong Province of Vietnam. The new taxon represents only the second genus of the tribe Caliscelini known from Vietnam. An identification key to separate Gelastissus Kirkaldy from Annamatissus gen. nov. is provided together with a check list of the Caliscelidae of Vietnam and their distribution. New distribution data in Vietnam are given for Cicimora sicildia Emeljanov, 1998 and Gelastissus hokutonis (Matsumura, 1916).